Clinical outcome and risk factors for subcutaneous emphysema in patients with lung cancer after video-assisted thorascopic surgery - Wang, Lei; Dong, Yingxian; Ji, Yanli; Song, Wenpeng; Cheng, Chao; Yang, Mei; Che, Guowei (Frontiers in Surgery, 2022)
【Abstract】 Background and purpose With the clinical application of minimally invasive surgery and concept of enhanced recovery after surgery (ERAS), the incidence of post-operative complications in lung cancer patients has been significantly reduced. However, postoperative subcutaneous emphysema (SE) becomes the main factor affecting the early discharge of patients. The aim of this study was to analyze the clinical outcome and risk factors for postoperative SE in lung cancer patients. Methods The clinical data of 414 lung cancer patients who were admitted to Department of Thoracic Surgery, West China Hospital, Sichuan University from September 2021 to December 2021 were prospectively collected. The incidence, severity and treatment of patients who had SE, surgery approach, application of drainage tube and clinical information were analyzed. Results The incidence rate of postoperative SE in patients with lung cancer was 33.09% (137/414) and mild cases accounted for the vast majority (30.19%, 125/414). Multivariate analysis indicated that male [odds ratio (OR)=2.247, P=0.014] and advanced age (OR=1.021, P=0.043) were main risk factors for postoperative SE in patients with lung cancer. Conservative treatment was the main treatment option for subcutaneous emphysema (98.5%, 135/137). The average hospital stay in the subcutaneous emphysema group (5.49±4.41 d) was significantly longer than that in the non-subcutaneous emphysema group (4.44±3.32 d) (P=0.014) and no significant statistical difference in the average total hospital cost between the two groups (7798.31±1414.85＄vs 7501.14±1605.18 ＄, P =0.072). Conclusion Postoperative subcutaneous emphysema in patients with minimally invasive lung cancer is mainly mild, and conservative treatment is appropriate for most cases.